2008
DOI: 10.1002/ptr.2535
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of beetroot juice and chips on oxidative metabolism and apoptosis in neutrophils from obese individuals

Abstract: Oxidative stress and inflammation are involved in the development of obesity. Beetroot (Beta vulgaris var. rubra) is a food ingredient containing betalain pigments that show antioxidant activity. The in vitro effect of beetroot juice and chips on oxidative metabolism and apoptosis in neutrophils from obese individuals has been investigated. Fifteen obese women (aged 45 ± ± ± ± ± 9 years, BMI > > > > >30 kg/m 2 ) and nine healthy controls (women, aged 29 ± ± ± ± ± 11 years, BMI = = = = = 22.2 ± ± ± ± ± 1.6 kg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(88 citation statements)
references
References 36 publications
4
77
0
7
Order By: Relevance
“…These findings go in line with reports showing an effect of other procyanidin-rich foods on diabetes [108], [109], [110]. Recent human studies also document that Aronia juice may be useful in in the treatment of obesity disorders [111].…”
Section: Antidiabetes Effectssupporting
confidence: 89%
“…These findings go in line with reports showing an effect of other procyanidin-rich foods on diabetes [108], [109], [110]. Recent human studies also document that Aronia juice may be useful in in the treatment of obesity disorders [111].…”
Section: Antidiabetes Effectssupporting
confidence: 89%
“…Furthermore, the levels of total phenolics (2.73-10.35 g/l) and total anthocyanins (0.10-0.67 g/l) estimated in this study agree with the literature data. Total phenolic content determined by the Folin-Ciocalteu method varied from 5.46 [31] to 18.54 g/l [32], while total anthocyanin content estimated by pH-differential method ranged from 0.15 [11] to 3.04 g/l [6]. The large differentiation noticed in both the present and previous studies may be due to differences in chokeberry cultivars, maturation stages as well as technology of juice production, and time of the juice storage.…”
Section: Discussionmentioning
confidence: 99%
“…Results of in vitro and in vivo studies indicate that chokeberry juice has cardioprotective [7,8], hepatoprotective [9], and anti-diabetic effects [1] as well as anticancer activity [10]. Recent human studies also showed that Aronia melanocarpa juice may be useful in the treatment of obesity disorders [11]. Black chokeberry constituents may help in reducing dietary fat absorption by inhibiting digestive lipases activity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major causes of the metabolic syndrome is excessive consumption of carbohydrates and triglycerides. Triglycerides can cause abnormal accumulation of body fat since it has the highest energy density (9 kcal/g) (Zielinska-Przyjemska et al 2009). One therapeutic approaches is to retard carbohydrates and lipids absorption by inhibiting the activity of the key digestive enzymes in the digestive system.…”
Section: Introductionmentioning
confidence: 99%